Examining Technology Self-Efficacy in Indonesian EFL Classrooms: Insights from Secondary School English Teachers - Apreliani Dwiastuti; Muamaroh; Yeny Prastiwi (Universitas Hamzanwadi, 2025)
Teachers’ technology self-efficacy significantly influences their ability to effectively adopt and utilize digital tools. However, many secondary school English teachers in Indonesia still face challenges adapting to technology, which may hinder their ability to integrate digital tools into their teaching practices. While existing studies primarily focus on teachers' perceptions, professional agency, and general challenges in technology integration, few explore how demographic factors—such as gender, age, education level, and teaching experience—affect technology self-efficacy among Indonesian secondary school English teachers. A descriptive quantitative design was employed, utilizing statistical analysis to interpret the data. The study involved 29 secondary school English teachers from the Jatinom English Teachers Association (JETA), Klaten, Central Java, Indonesia. Data were collected using the Technology Self-Efficacy Scale (Wang et al., 2004) via Google Forms. The findings revealed that teachers' technology self-efficacy was moderate overall. Male teachers aged 26-30 demonstrated higher confidence in ICT usage. Additionally, teachers with a Bachelor's degree exhibited higher technology self-efficacy than those with a Master’s degree, suggesting that formal education level alone does not directly influence confidence in using technology. Furthermore, teachers with 11-15 years of experience reported the highest self-efficacy, while those with 1-5 years of experience had the lowest, indicating that teaching experience alone is not a strong determinant of technology self-efficacy. These results highlight the need for improved ICT infrastructure and professional development training to enhance teachers’ confidence and skills in technology use.